(untitled) (Itinera, 2025)
This article examines the intersection of aesthetics, memory, and technopolitics through a critical analysis of the Vajont disaster and Giovanni Michelucci’s Chiesa Monumentale di Santa Maria Immacolata in Longarone. It explores how Michelucci’s controversial project, built on the site of a village church destroyed by the 1963 Vajont disaster, responds to the physical, environmental, and symbolic violence of the nearby Vajont dam, an emblem of the Italian technosphere and extractivist modernity. The disaster, caused by the collapse of Monte Toc into the dam’s reservoir, represents a catastrophic failure rooted in the technocratic disregard for local and environmental semiotics in favor of technological abstraction. Drawing on the works of Marco Armiero, Peter K. Haff, and Gilles Deleuze, the article analyzes two competing semio-epistemic regimes: one grounded in dominance and blindness to natural and local signs; the other, in contemplative attention to presence and absence. The latter regime, exemplified by Michelucci’s church, represents a new aesthetic paradigm for post-disaster remembrance through architecture. Accordingly, the article proposes a radical alternative to the aesthetics of epistemic control, reimagining community as a shared openness to loss rather than as a monument that recreates a fixed past.